In-depth understanding of intra-household decision-making in the cassava value chain in Tanzania - Mwakanyamale, Devis F.; Liani, Millicent L.; Cole, Steven M. (International Institute of Tropical Agriculture, 2023)
Existing studies provide insights into understanding intrahousehold decision-making, focusing on who makes decisions on agricultural matters in low-income country contexts. However, little is known about the underlying processes concerning who performs which specific agricultural tasks, who makes decisions in those tasks, and how and why they do so. Our study used in-depth interviews with 37 marital dyads involved in cassava value-chain work in Tanzania. Findings highlight that women engage in cassavarelated activities, yet do not necessarily hold exclusive decision-making powers in these tasks. Decisions concerning activities performed by both spouses are made jointly or by men, while women primarily make decisions on matters when they possess the most knowledge. Decisions on the use of income from cassava are mainly made jointly. Women are more involved in expenditure decisions on household food and nutrition security, whereas men decide on matters related to purchasing farm inputs and high-value assets. The reasons why men make sole decisions are attributed to their traditional role as household heads. Joint decisions are made to avoid misunderstandings or promote cooperation within the household. Women in monogamous marriages and in similar age groups with their spouses are more likely to participate in decision-making processes. For dyads in polygynous relationships, we observe differences between younger and older couples, with decision-making authority exercised by men in the latter. We argue that an indepth understanding of decision-making processes within agricultural households can better inform the design of value-chain development interventions aimed at promoting gender equality and empowering women.